An evaluating study on ESP medical textbook: instructors and learners needs analysis - Salehi, Hadi; Khadivar, Zahra; Babaee, Ruzbeh; Jujar Singh, Hardev Kaur (Canadian Center of Science and Education, 2015)
Textbook evaluation is determining the productivity and value of textbooks with respect to stated objectives, standards, or criteria. This study was an attempt to evaluate the ESP medical textbook, which is taught at some universities in Iran. To gather the necessary data, two researcher-made questionnaires and one interview protocol were used. Iranian Medical instructors and learners answered to a 28-item questionnaire to express their attitudes towards the content, exercises, and topics of their ESP course book. In addition, some members of both groups participated in an interview to gain in depth information about the study. They were both male and female. The findings revealed that the content and the topics of the ESP medical textbook are based on the learners and instructors’ needs. The results of this study have a number of implications for medical instructors, learners, and syllabus designers.